Is Geology Scaling?. Issue 9 (24th September 2019) - Dimri, V.P.; Srivastava, R.P.
Abstract: Concept of fractals and power law in statistical and geometrical data sets is rather matured. However, the application part of the fractal theory is not yet commensurate with the theoretical literature available. In this invited review, we take a dig at the range of data sets to demonstrate their fractal/scaling behavior for instance well logs and geological features such as fractures, which exhibit scaling behavior. The range of topics discussed in this paper are based on the concept that physical and geometrical property of the Earth follows scaling behavior. Based on the observations and available research we aim to address the question "Is geology scaling?" Further, we elaborate on one of the applications of fractal concepts in designing an operator for the colored inversion of seismic data, which is very efficient, and does not need a background model to do the seismic inversion in contrast to classical seismic inversion methods. Key Points: Article provides robust application of scaling law for interpretation of geophysical and geological data Methods to understand if given data set follows scaling behavior is discussed with examples